Logit Estimates of Strike Incidence from Canadian Contract Data - Gunderson, Morley; Kervin, John; Reid, Frank (Journal of Labor Economics, 1986)
Logit estimates of strike incidence are made based on a unique and comprehensive data set of 2,437 collective agreements-the appropriate level of aggregation since that is where bargaining occurs. The results are interpreted through a theoretical framework emphasizing that strikes are more likely when the joint costs of using the strike mechanism are low relative to the cost of alternative mechanisms for achieving the same purposes. Such functions of strikes are to generate information, elicit truth telling, establish reputations, provide catharsis, and solve intraorganizational conflict.